Emergent infection: atypical clinical cases of monkeypox (updated review) - Sydorchuk, Aniuta; Horbachova, Oksana (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2023)
Abstract. The international emergency caused by monkeypox has forced the world to pay attention to this infection, as it has spread beyond endemic regions and no control measures have been developed. The virus began to be transmitted to humans not only by contact, but also by airborne droplets, fecal-oral, and vertical. There have been cases of in-hospital spread, outbreaks after eating contaminated animal meat, and swimming in water. Pregnant women, children under 8 years of age, and HIV-infected people require special attention due to the risk of complications. Therefore, it is important for doctors of all levels to be aware of new ways of spreading the infection, atypical manifestations of the disease for differential diagnosis, timely detection and further treatment. Aim. To conduct an up-to-date literature review of clinical cases of monkeypox in people at increased risk of developing atypical course and complications - in HIV-infected people (due to the virus’s damage to the immune system) and children under 8 years of age (due to insufficiently formed immunity). Materials and Мethods. Scientific articles from the google scholar database were analyzed, among which 7 articles with 9 different case descriptions were selected to conduct an in-depth study of clinical cases among people from different non-endemic countries who have insufficient immunity (WHO experts consider African and Asian countries to be endemic). Results. Most of the atypical cases were observed among homosexual men receiving antiretroviral therapy or pre-exposure prophylaxis for HIV infection. The characteristic rash appeared after unprotected oral or anal sex on the corresponding body parts. As for the disease in young children who do not have their own immunity, the mechanism of transmission was contact or vertical. Conclusions. Our analysis of the literature shows the prevalence of monkeypox in the male gender group with non-traditional sexual orientation. Based on the analysis, HIV-infected homosexuals, mostly men, are the main risk group for infection with this emergent orthopoxvirus. At the same time, people with primary and secondary immunodeficiency conditions remain particularly vulnerable. It is important that the atypical clinical course complicates timely clinical and laboratory diagnosis and even the initiation of treatment, which can lead to severe and fatal complications (in endemic regions among children and debilitated HIV-infected persons). It is advisable to take timely anti-epidemic measures with the implementation of specific prophylaxis for vulnerable categories of persons (listed above, as well as occupational risk groups), along with an increase in epidemic surveillance and strict infection control in compliance with International Health Regulations at checkpoints along the entire state border.